Modeling of Ni2+ exchange on the strong acid ion-exchange resin and the organic-inorganic ionite - Afonin, Gennadiyy; Beznosyk, Yuriy; Dzyazko, Yuliyia (Lviv Polytechnic Publishing House, 2015)
In dynamic conditions extraction of ions of Ni2+ from the combined solution with using of acid ion-exchange gel pitch and the composite ionite on its basis containing units of nanoparticles of hydrophosphate of zirconium is investigated. The model allowing to define time for which capacity of Ni2+ ions is ful offered. The model assumes use only of empirical parameters reflecting concoction of ions in a firm phase.
Keywords: ion exchange treatment of water; the nickel ions; calcium; magnesium; dynamic model